Comparative study of cord blood lipid profile in preterm and post term neonates - Pradeep, Pooja; T., Arunkumar; S., Sundari (International Journal of Contemporary Pediatrics, 2019)
Background: The fetal-origin hypothesis and fetal programming emphasize the profound and sustained impact of factors related to fetal health on the development of chronic disease in adulthood. Several studies suggested that low birth weight and preterm birth linked to abnormalities in cord lipid profile and higher prevalence of atherosclerotic cardiovascular disease. Authors objectives was to estimate and compare cord lipid profile in term, pre-term, and post-term neonates. Methods: In the study group, there were 200 healthy Polish newborns. Newborn characteristics included sex, gestational age at birth, Apgar score, and anthropometric data (weight and length at birth, neonatal ponderal index, head, chest and abdominal circumferences, placental weight, and placental-fetal weight ratio). Cord blood samples were collected for total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglycerides (TG). Information regarding selected maternal factors was collected. Neonates were classified into preterm (<37 weeks) and term (≥37 weeks) based on new Ballard scoring. Results: The preterm had higher Total cholesterol compared to Term and post term and it was Statistically Significant with a p value of < 0.001. The preterm had higher Triglycerides compared to term and post term and it was statistically significant with a p value of <0.01. The preterm had higher HDL compared to Term and post term and it was statistically significant with a p value of <0.001. The preterm had higher LDL compared to Term and post term it was statistically significant with a p value of <0.001. The preterm had higher VLDL compared to Term and post term and it was statistically significant with a p value of <0.01. Conclusions: Abnormal intrauterine milieu created by maternal changes during gestation may bear a profound impact on lipid metabolism in neonates, which may account for their differences in lipid profile and anthropometry at birth.